TEOLOGI KRISTEN SEBAGAI LANDASAN PEMBARUAN IMAN DAN ETIKA DALAM MEWUJUDKAN TRANSFORMASI PRIBADI, GEREJA, DAN KEHIDUPAN SOSIAL MASYARAKAT - Kristina Sesa; Mirsa Triwani; Melda Loto’; Imanuel Gelvin Sariri; Rusliana Toban (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This article examines the role of Christian theology as a foundation for the renewal of faith and ethics in order to realize the transformation of individuals, the church, and the social life of society. This research uses a qualitative approach with a library study method through analysis of theological literature, Christian ethics, and relevant academic writings. The results of the study indicate that Christian theology functions not only as a dogmatic reflection but also as a practical guideline for believers. First, Christian theology strengthens faith by deepening understanding of salvation in Christ, which encourages personal renewal. Second, the integration of theology and Christian ethics makes faith manifest in acts of love and moral responsibility in daily life. Third, theology plays a crucial role in the transformation of the church, both in renewing spirituality, strengthening fellowship, and affirming the prophetic role amidst global challenges. Fourth, Christian theology emphasizes the social responsibility of the congregation in building a just, peaceful, and solidary society. Thus, this article confirms that Christian theology has a significant contribution not only in the development of personal faith but also in bringing about meaningful social change in society.